Contextual Differential Strategy in Muhammadiyah Education Quality Asahan: Strategi Kontekstual Diferensial dalam Mutu Pendidikan Muhammadiyah Asahan - Hadi Akmal Lubis; Atok Miftachul Hudha; Moh. Mahfud Effendi (Academia Open, 2026)
General Background: Education quality has shifted from output metrics toward institutional adaptability in producing relevant and competitive graduates amid global and technological disruption. Specific Background: Muhammadiyah private schools in Asahan Regency face dual demands to meet national standards while maintaining competitiveness with limited resources, especially across differing mandates of SMA and SMK. Knowledge Gap: Prior studies rarely provide comparative multi-case analysis distinguishing quality improvement strategies between general and vocational Muhammadiyah schools in specific regional contexts. Aims: This study aims to analyze and construct a strategic model of education quality improvement through a multi-case comparison of SMA and SMK Muhammadiyah in Asahan. Results: The findings reveal a Contextual-Differential Strategy Model based on two pillars: convergence in Al-Islam Kemuhammadiyahan values and teacher professionalism, and divergence in institutional focus, where SMA prioritizes academic pathways to higher education while SMK emphasizes industrial partnerships and work readiness. Novelty: The study introduces a pluralistic and goal-oriented perspective of education quality, rejecting uniform management approaches and emphasizing strategic differentiation within a shared organizational framework. Implications: The model provides a practical framework for policy formulation and school governance, promoting adaptive, context-based resource allocation and strengthening institutional identity to sustain competitiveness in regional education systems Highlights• Identifies dual strategic pillars combining shared values with operational differentiation• Demonstrates distinct institutional focus between academic and vocational pathways• Proposes adaptive governance framework based on contextual resource allocation KeywordsEducational Quality; Contextual Differential Strategy; Multi Case Study; Muhammadiyah Education; Asahan Regency